Unveiling the impact of second-order 1H-17O Quadrupolar-Dipolar interaction on solid-state NMR spectroscopy - Yi Ji; Kuizhi Chen; Aijing Hao; Guangjin Hou (Journal of Magnetic Resonance Open)
Recent advances in the 17O-enrichment techiques and high-resolution nuclear magnetic resonance (NMR) methods have opened new opportunities to utilize 17O NMR to disentangle the zeolitic structure−property relationship that has not been well resolved through traditional 1H, 27Al, and 29Si NMR spectroscopy. Compared with one-dimensional 17O magic angle spinning (MAS) NMR experiments, 1H-17O correlation spectrocopy has become a crucial method for revealing the structures and dynamics of reactive hydroxyl species in zeolites with higher resolution and precision. However, the introduction of 17O can induce changes in 1H MAS NMR signals due to the second-order 1H-17O quadrupolar-dipolar (2nd-QD) cross interaction, which has recently been revealed by us on H-ZSM-5 (H-MFI) zeolites with 10-membered-ring (MR) channels. Herein, we performed various 1H-17O correlation experiments (1H{17O}-J-heteronuclear multiple quantum coherence (HMQC), 1H{17O}-D-HMQC, and 1H→17O-D-RINEPT) on two other types of 17O-enriched zeolites, i.e., H-Mordenite (H-MOR) with 8-/12-MR channels and H-ZSM-35 (H-FER) with 8-/10-MR channels. Notably, unusual 1H-17O correlation signals with tilted patterns and magnetic-field-dependent shifts were observed on both samples and all tested correlation experiments at high fields up to 18.8 T. These observations were further comprehensively explained by theoretical analysis of the 1H-17O quadrupolar-dipolar interaction, thus demonstrating that the 1H-17O 2nd-QD interaction generally affects the 1H and 1H-17O correlation MAS NMR spectra of the dehydrated 17O-enriched zeolites, irrespective of the framework types. Beyond zeolites, the non-ignorable 2nd-QD interaction on NMR spectroscopy can complicate NMR identification of 17O-labeled hydroxyls in many other inorganic materials and biomolecules. The analysis methods proposed in this study are expected to effectively address these challenges and provide clearer insights into such systems.